Conditions for successful interprofessional collaboration in integrated care – Lessons from a primary care setting in Denmark. Issue 4 (April 2021) - Hald, Andreas Nielsen; Bech, Mickael; Burau, Viola
Highlights: Conditions in general greatly influence the staff's perceived success of interprofessional collaboration. Context conditions greatly influence intervention conditions at the professional and organisational level. The professional and organisational level co-variate for both intervention and context conditions. Professional level context conditions have the biggest influence on staff's perceived success. Policymakers and researchers in health care should increase their focus on context. Abstract: Introduction: Increasing demand for interprofessional collaboration in health care settings has led to a greater focus on how conditions influence the success of interprofessional collaboration, but little is known about the magnitude of the interactions between different conditions. This paper aims to examine the relationships of intervention conditions and context conditions at the professional and organisational level and examine how they influence the staff's perceived success of the interprofessional collaboration. Methods: The study was conducted as a multilevel cross-sectional survey in March of 2019 in the second largest municipality in Denmark, Aarhus. The study population was all frontline-staff members and managers in nursing homes, home care units and health care units. The final sample consisted of 498 staff members and 27 managers. Confirmatory path analysis was used to analyse the data. Results: The results indicate that context conditions greatly influence intervention conditions at the professional and organisational level and that the professional and organisational levels moderately co-variate. Professional level context conditions have the biggest influence on staff's perceived success, partly because its influence is confounded by intervention conditions. Conclusion: Practice and research in health care settings should re-focus their attention from a broad understanding of context as unchangeable and inconsequential, to understanding context as an important condition type for interprofessional collaboration that needs to be further understood and researched.